The Effectiveness of Successful Intelligence Training on Academic Engagement and Academic Resilience in High School Students - Zeinab Bazzi; Gholamhasan Panahi (Iranian Evolutionary Educational Psychology Journal, 2023)
The present study aimed to examine the effectiveness of successful intelligence training on the academic engagement and academic resilience in high school students. The current research is a pretest-posttest semi experimental design with a control group. The statistical population included all female high school students of Zahedan city (Iran) in 2022. Participants were 30 female high school students selected by purposive sampling and randomly assigned to experimental and control groups (15 people in each group). Successful intelligence educational package (Babaei, 2015) was carried out in the experimental group during 10 sessions of 90 minutes. The research tools were Academic Engagement Inventory (Salmela-Aro & Upadaya, 2012) and Academic Resilience Scale (Samuels, 2004). The reliability of the research questionnaires was estimated using Cronbach's alpha coefficient of 0.79 for the academic engagement inventory and 0.91 for the academic resilience scale. The results revealed that successful intelligence training had a positive effect on students' academic engagement (and its components) and academic resilience (and its components) in female high school students. The findings emphasize the importance of considering the cognitive interventions that contributes to the ongoing enhancement of academic engagement and academic resilience as the motivational constructs in educational setting.